State-of-the-Art Direct (13)C and Indirect (1)H-[(13)C] NMR Spectroscopy In Vivo: A Practical Guide - de Graaf, Robin A. (2011)
Carbon-13 NMR spectroscopy in combination with (13)C-labeled substrate infusion is a powerful technique to measure a large number of metabolic fluxes non-invasively in vivo. It has been used to quantify glycogen synthesis rates, establish quantitative relationships between energy metabolism and neurotransmission and evaluate the importance of different substrates. All measurements can, in principle, be performed through direct (13)C NMR detection or via indirect (1)H-[(13)C] NMR detection of the protons attached to (13)C nuclei. The choice for detection scheme and pulse sequence depends on the magnetic field strength, whereas substrate selection depends on the metabolic pathways that are studied. (13)C NMR spectroscopy remains a challenging technique that requires several non-standard hardware modifications, infusion of (13)C-labeled substrates and sophisticated processing and metabolic modeling. Here the various aspects of direct (13)C and indirect (1)H-[(13)C] NMR are reviewed with the aim of providing a practical guide.